The reason for a high Ca2+-sensitivity associated with Arg91Gly substitution in TPM2 gene is the abnormal behavior and high flexibility of tropomyosin during the ATPase cycle - Borovikov, Y; Simonyan, A; Karpicheva, O; Avrova, S; Rysev, N; Sirenko, V; Piers, A; Redwood, C (Elsevier, 2017)
Substitution of Arg for Gly residue in 91th position in β-tropomyosin caused by a point mutation in TPM2 gene is associated with distal arthrogryposis, characterized by a high Ca2+-sensitivity of myofilament and contracture syndrome. To understand the mechanisms of this defect, we studied multistep changes in mobility and spatial arrangement of tropomyosin, actin and myosin heads during the ATPase cycle in reconstituted ghost fibres, using the polarized fluorescence microscopy. The mutation was shown to markedly decrease the bending stiffness of β-tropomyosin in the thin filaments. In the absence of the myosin heads the mutation did not alter the ability of troponin to shift tropomyosin to the blocked position and to switch actin monomers off at low Ca2+. During the ATPase cycle the movement of the mutant tropomyosin is restrained, it is located near the open position, which allows strong binding of the myosin heads to actin even at low Ca2+. This may be the reason for both high Ca2+-sensitivity and contractures associated with the Arg91Gly mutation. The use of reagents that decrease the Ca2+sensitivity of the troponin complex may not be appropriate to restore muscle function in patients with this mutation.